(untitled) (Tanzania Journal for Population studies and Development, 2025)
This research paper examines the impacts of changing climate and non-climatic factors on crop production in Bahi District, Tanzania, to reveal the complexities of agricultural challenges in the district. The study used a mixed-method design, combining quantitative and qualitative approaches. Primary data was collected through 254 household interviews, three focus group discussions, and 30 key informant interviews. Secondary data was gathered through a literature review from published and unpublished sources. Quantitative data analysis was conducted using Excel 2010 to generate graphs and tables for descriptive data, while inferential data were analysed using chi-square in SPSS version 20 to explore the relationship between variables. The trends in crop production were assessed using the Man-Kendall analysis. The study highlights that climate change negatively affects crop production through reduced crop yields, increased pest and disease incidence, and stunted plant growth. Also, the study revealed non-climatic stressors affecting crop production, such as lack of capital, poor government support, water scarcity, and lack of practical knowledge. Climate change factors overshadow non-climatic factors in affecting crop production. Therefore, several adaptation strategies should be promoted to reduce the adverse effects of climate change and non-climatic stressors on crop production.